The Role of Blockchain Technology in Ensure Transparency Chain Supply Product Agriculture Organic - Faozi Muhamad (Politeknik Siber Cerdika Internasional, 2025)
Transparency and traceability information in chain supply product agriculture organic become challenge main in guard trust Consumers and the integrity of organic labels . Research This aim For explore role blockchain technology in ensure data transparency and validation of distribution processes product organic . The method used is approach qualitative through studies field against 15 perpetrators chain supplies , including farmers , cooperatives , distributors, and agritech startups . Research results show that blockchain is capable of increase traceability products , speed up the audit process, and build system more reporting​ trusted . Although adoption technology This Still face obstacle like limitations digital literacy and infrastructure , potential its integration very big especially at the level cooperatives and retail. Research This give implications practical for development system chain supply agriculture based technology as well as push collaboration cross actor For build system more food​ transparent and accountable .